2015
DOI: 10.1115/1.4030217
|View full text |Cite
|
Sign up to set email alerts
|

Pool Boiling Enhancement by Electrohydrodynamic Force and Diamond Coated Surfaces

Abstract: Boiling heat transfer enhancement via compound effect of the electrohydrodynamic (EHD) effect and microstructured surfaces has been experimentally and analytically investigated. A fluorinated dielectric liquid (Asahi Glass Co., Ltd., AE-3000) was selected as the working fluid. Pool boiling heat transfer in the saturated liquid was measured at atmospheric pressure. Microstructured surfaces, which are mainly used for cutting tools, were developed with diamond particles using electrodeposition technique. Four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The boiling surface was electrically deposited with fine diamond particles (particle diameters of 20 and 1.5 m) to enhance the boiling heat transfer. Kano (2015) revealed that diamond electrodeposited boiling surface enhances boiling heat transfer and increases CHF by 40 % and HTC by 90 %, comparing with a smooth copper surface without electric filed since the diamond particles served as nucleation sites. In addition, the increased density of the nucleation sites resulted in reduction of superheat when CHF occurred.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The boiling surface was electrically deposited with fine diamond particles (particle diameters of 20 and 1.5 m) to enhance the boiling heat transfer. Kano (2015) revealed that diamond electrodeposited boiling surface enhances boiling heat transfer and increases CHF by 40 % and HTC by 90 %, comparing with a smooth copper surface without electric filed since the diamond particles served as nucleation sites. In addition, the increased density of the nucleation sites resulted in reduction of superheat when CHF occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Extended surfaces in MCs are categorized as passive methods, while fluid vibration, vapor suction, and application of AC or DC electrostatic fields are categorized as active methods. Electrohydrodynamic (EHD) force generated by the application of an electric field has been mainly studied as an active enhancement method (Johnson, 1968;Darabi and Ekula, 2003;Moghaddam and Ohadi, 2005;Pearson and Sayed-Yagoobi, 2013;Kano and Takahashi, 2013;Kano, 2014;Kano, 2015;Patel and Sayed-Yagoobi, 2017;Kano and Okamoto, 2017;Kano, 2019). Kano (2019) developed a micro-slit channel (MSC) as a cooling system providing active flow boiling heat transfer by applying a high electric field, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation